Pandemics and their social repercussions throughout history associated with the new SARS-COV-2: A review study (Research, Society and Development, 2021)
With great apprehension, the world is now witnessing the birth of a new pandemic. SARS-COV-2, which already causes tremendous suffering, death and disturbance of normal life. Uncertainty and fear are exacerbated by the belief that what we are experiencing is new and mysterious. However, deadly pandemics and disease emergencies are not new phenomena, they have challenged human existence throughout history. The objective of this work was to search in the scientific literature what has been produced on the subject as well as to illustrate the repercussions of the great pandemics. Method: This is an integrative literature review, which followed the PICO strategy to identify the repercussions of pandemics on humanity. The search for articles was carried out within the databases of the journals Pubmed / Medline, BVS / Lilacs and Scielo. The descriptors used were “history” AND “pandemics” AND “pest” AND “prevention and control with full texts, published between 2011 and 2021, in English, Portuguese and Spanish and the Boolean operator AND was used. Results: 108 articles were found. 32 articles were selected to be read in full and 10 met the criteria of this review. Conclusion: Evidence shows that epidemics and pandemics have their understanding and responses related to the intellectual context of their respective times, but they also shape the social, political and theological thinking, prevalent in the years that follow.